Employability and marketability of the graduates of Islamic studies in Islamic banking and finance: Malaysian experience - Kayadibi, Saim (2011)
This paper attempts to explore the role played by Islamic Studies in the areas of Islamic economical and financial education at Higher Educational Institutions for employability and marketability of the graduates particularly, in facing the challenges of the issues of globalization. This desirable change of trend in teaching and learning is closely linked with the emergence of Islamic Banking systems and institutions, which are widespread in Islamic Countries and have even entered into the majority non-Muslim countries.